Contribution of National Health Insurance Patient Revenue to Financial Performance of Private-Profit Hospitals from 2017 to 2022 - Imansyah, Fadlul; Sjaaf, Amal Chalik; Nadjib, Mardiati; Hartini, Rina (UI Scholars Hub, 2025)
This study investigated the relationship between National Health Insurance (NHI) patient revenue and profit-private hospital financial performance in Indonesia. As the NHI provider, Badan Penyelenggara Jaminan Sosial (BPJS) Healthcare Security’s influence on hospital revenues has raised concerns about its impact on financial sustainability. This study used financial performance indicators to develop a financial performance index—Return on Assets (ROA), Return on Equity (ROE), Earnings Before Interest, Taxes, Depreciation, and Amortization (EBITDA) Margin, Current Ratio, and Net Profit Margin (NPM)—to assess the financial impact of BPJS Healthcare Security revenue. A partial model approach of multiple linear regression was employed using secondary data from seven private-profit hospitals listed on the Indonesian Stock Exchange from 2017 to 2022. The findings indicated a negative correlation between BPJS Healthcare Security patient revenue and the hospital financial performance index. Specifically, higher patient revenue correlated with lower performance across key financial indicators, including ROA, ROE, EBITDA Margin, Current Ratio, and NPM. It was essential for hospitals but not necessarily to improve their financial health performance. Hospitals need to optimize their revenue mix and explore alternative financial strategies to enhance performance.